ANALISIS SIKAP SOSIAL SISWA DALAM PEMBELAJARAN TEMATIK PADA KELAS II SDIT CORDOVA 2 - Yeni Nuraeni; Anita Dewi; Nanda Audia; Putri Shafa Harfiantika; Lola Andika Rahmadany (Sindoro: Cendikia Pendidikan, 2025)
A person has a social attitude, which can be defined as their awareness of determining their behavior or actions in real life regarding social matters. Social attitudes can also be defined as mutually uniting individuals in society, such as helping, respecting and caring about the environment. The aim of this research is to evaluate students' social attitudes towards thematic lessons taught in class II. This research uses a descriptive qualitative approach, which uses data collection methods such as observation, interviews and documentation. The data obtained was analyzed using the steps of data collection, data reduction, data presentation and drawing conclusions. The subjects of this research were 7 people consisting of 6 class II students and 1 class II homeroom teacher. The research results showed that students' social attitudes during thematic learning increased in terms of honesty, discipline, responsibility, politeness and caring. According to this research, students' social attitudes are very important for their preparation when they interact with other people and live in society. The conclusion is that thematic learning can help students develop their own social attitudes.